DNA/Protein Binding, Molecular Docking and Cytotoxicity Studies of Piperazinyl‐Moiety‐Based Copper(II) Complexes. Issue 31 (22nd August 2018) - Mistri, Soumen; Patra, Apu; Santra, Manas Kumar; Paul, Debasish; Zangrando, Ennio; Puschmann, Horst; Manna, Subal Chandra
Abstract: Copper(II) complexes [Cu(HL)(ClO4 )(H2 O)](ClO4 )⋅3H2 O (1 ), [Cu(HL)( m ‐phth)]⋅5H2 O (2 ) and [Cu(HL)(NCS)]2 (ClO4 )2 ⋅2H2 O (3 ) (HL=2‐[2‐(1‐piperazinyl)ethylimino]methylphenol; m ‐phth=1, 3‐benzenedicarboxylate] have been synthesized and characterized by structural determination and spectroscopic studies. The mononuclear square pyramidal complex1 resulted from the reaction of HL with copper perchlorate hexahydrate. Then mononuclear square planar complex2 and dinuclear thiocyanato bridged complex3 were obtained by reacting1 with disodium 1, 3‐benzenedicarboxylate (Na2 ( m ‐phth)) and potassium thiocyanate, respectively. The interactions of1–3 with CT‐DNA / serum albumins were investigated by UV‐visible absorption and fluorescence spectroscopy. The intrinsic binding constants of1, 2 and3 with CT‐DNA were calculated as 1.44 (±0.13) × 10 5, 4.86 (±0.11) × 10 5 and 4.51 (±0.16) × 10 5 L mol −1, respectively. Study of the interactions of1–3 with human serum albumin (HSA) / bovine serum albumin (BSA) showed that all the complexes could quench intrinsic fluorescence of HSA and BSA through a static quenching process. Molecular docking technique was utilised to confirm the mode of interaction of complexes with CT‐DNA / serum albumin. Anticancer activities of the complexes have been tested using human breast cancer cell lines MCF7 and MBA‐MB‐231. Among the complexes studied3 shows the higher cytotoxic activity and growth inhibition of cancer cells via induction of apoptotic cell death. Abstract : Copper(II) complexes, [Cu(HL)(ClO4 )(H2 O)](ClO4 )⋅3H2 O (1 ), [Cu(HL)( m ‐phth)]⋅5H2 O (2 ) and [Cu(HL)(NCS)]2 (ClO4 )2 ⋅2H2 O (3 ) (HL= 2‐[2‐(1‐piperazinyl)ethylimino]methylphenol; m ‐phth=1, 3‐benzenedicarboxylate] have been synthesized and structurally characterized. UV‐vis absorption and fluorescence spectroscopic studies revealed that these complexes significantly interact with CT‐DNA and serum albumins. Of the complexes studied, 3 exhibits the higher cytotoxicity activity and inhibits the growth of cancer cells by apoptosis.